IITA Research highlights for 1982 (Ibadan International Institute for Tropical Agirculture, 1982)
The publication comprises of highlights of researches conducted by IITA Ibadan in 1982. These researches were conducted in the humid forest, transitional, and savannah zones of Nigeria. Areas included root and tuber crops, farming systems, grain legumes, cereals and training.
lje 13/06/17
Loans
Keywords: Agriculture-Tropical; Agriculture-Nigeria